2022
DOI: 10.1002/ajoc.202200196
|View full text |Cite
|
Sign up to set email alerts
|

Peptide‐Heterocycle Conjugates as Antifungals Against Cryptococcosis

Abstract: In last three decades, only one new USFDA approved antifungal drug (echinocandin) was introduced into the clinics. The identification of new scaffolds with novel mechanisms of action is an important goal of current antifungal research. Herein, we describe the design, synthesis and in vitro antimicrobial activities of heterocycle-His(2-aryl)-Arg-NHBzl conjugates as a new structural class of peptidomimetics with promising antifungal activity against Cryptococcus neoformans (IC 50 values ranging between 2.13-14.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In 2022, Chen et al unveiled a Pd-catalyzed method for post-assembly peptide CÀ H functionalization utilizing the native side-chain of methionine (Met) (Scheme 6). [74] β-Arylation and γ-arylation of peptides were achieved in moderate yields, with optimized conditions yielding the desired arylation products (23-24) from model peptides (21)(22) with excellent diastereoselectivity (> 20:1) by the α,β-trans-configured 6-membered palladacycle intermediate (25). Notably, electron-rich aryl iodides provided higher yields compared to electron-deficient ones.…”
Section: Methionine-directed Functionalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2022, Chen et al unveiled a Pd-catalyzed method for post-assembly peptide CÀ H functionalization utilizing the native side-chain of methionine (Met) (Scheme 6). [74] β-Arylation and γ-arylation of peptides were achieved in moderate yields, with optimized conditions yielding the desired arylation products (23-24) from model peptides (21)(22) with excellent diastereoselectivity (> 20:1) by the α,β-trans-configured 6-membered palladacycle intermediate (25). Notably, electron-rich aryl iodides provided higher yields compared to electron-deficient ones.…”
Section: Methionine-directed Functionalizationmentioning
confidence: 99%
“…Several techniques are available to improve the druggability and ADME of peptides. [17] This includes late-stage CÀ H functionalization, [18] backbone modification, [19] modification of the N-or C-terminus, [20][21] heterocyclic conjugation, [22] macrocyclization using head-to-tail via cross coupling, [23] and amide bond bio-isosteric replacement, [24] along with the incorporation of noncanonical [25] or modified amino acids. [26][27] Late-stage CÀ H functionalization of peptides has gained significant attention in recent years due to its potential applications in drug discovery, chemical biology, and material science.…”
Section: Introductionmentioning
confidence: 99%
“…147 More recently, in the quest for the development of potent and promising analogs as antimicrobials led to the identification of several other structural classes of peptides. Several series of N-1 arylated 148 and N-1 benzylated 149 histidine containing peptides along with peptides conjugated with heterocyclic analogs 150 were explored and identified as potent anticryptococcal agents.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Furthermore, in 2022, Jain et al reported their work on peptide-heterocycle conjugates for the treatment of cryptococcosis, [ 77 ]. A total of twelve analogs were synthesized, with the derivatives being based upon a histidine-arginine backbone.…”
Section: Introductionmentioning
confidence: 99%